2015
DOI: 10.1016/j.rchipe.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de morbilidad otorrinolaringológica en niños con síndrome de Down

Abstract: This series shows a high rate of ENT disorders in children with DS, which supports recommendations for hearing screening, high suspicion of obstructive sleep apnea and routine referral to an ENT specialist for prevention and aggressive therapy in order to reduce hearing loss and improve development of the child with DS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
0
1
0
14
Order By: Relevance
“…In this study, the five cases of laryngotracheomalacia were not associated with congenital heart disease and showed positive clinical progress. Paul et al (2015) observed that 78.8% of children with DS had ear-nose-throat disorders, and the most frequent disorders were allergic rhinitis (51.5%), and otitis media with effusion (44.8%). These fig-…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the five cases of laryngotracheomalacia were not associated with congenital heart disease and showed positive clinical progress. Paul et al (2015) observed that 78.8% of children with DS had ear-nose-throat disorders, and the most frequent disorders were allergic rhinitis (51.5%), and otitis media with effusion (44.8%). These fig-…”
Section: Discussionmentioning
confidence: 98%
“…Otras morbilidades crónicas como vicios de refracción, problemas dermatológicos y traumatológicos, SAHOS y epilepsia fueron reportados en nuestra serie con similar frecuencia a lo publicado en la literatura 28,29 , lo que motiva a tener equipos multidisciplinarios capacitados y al día con las recomendaciones internacionales para el cuidado en salud de los adolescentes con SD.…”
Section: Discussionunclassified
“…El SD es la anomalía cromosómica, más frecuente en recién nacidos y ocurre por la presencia de material genético adicional del cromosoma 21 (7) . Se han descrito tres tipos de alteraciones en el cromosoma 21 ocurridas durante la división celular resultando en SD con efecto similares, la forma más común es la trisomía (94%), es decir un cromosoma extra.…”
Section: Síndrome De Downunclassified
“…Un 4% presenta translocación de un segmento del cromosoma y sólo un 2% presenta mosaico, en donde solo algunas células presentan trisomía del cromosoma 21 (8) . Se presenta en 1 de cada 600 a 700 nacimientos (7) . De acuerdo con el estudio colaborativo latinoamericano de malformaciones congénitas en Latinoamérica, entre 1982 y el 2001 se registró en un promedio nacional en Chile de 1 × 500 nacido vivo en Chile, con una tasa para Santiago de 2.5 × 1000 nacidos vivos, una incidencia en ascenso en las dos últimas décadas (9)(10)(11) .…”
Section: Síndrome De Downunclassified
See 1 more Smart Citation